2019
DOI: 10.3390/insects10050126
|View full text |Cite
|
Sign up to set email alerts
|

Life History Effects Linked to an Advantage for wAu Wolbachia in Drosophila

Abstract: Wolbachia endosymbiont infections can persist and spread in insect populations without causing apparent effects on reproduction of their insect hosts, but the mechanisms involved are largely unknown. Here, we test for fitness effects of the wAu infection of Drosophila simulans by comparing multiple infected and uninfected polymorphic isofemale lines derived from nature. We show a fitness advantage (higher offspring number) for lines with the wAu Wolbachia infection when breeding on grapes, but only where there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Apart from their direct manipulation as suggested above, the involvement of both the IIS and hypoxia signaling pathways as a consequence of Wolbachia infection opens up several exciting avenues for further discovery. Given the strain-host specificity discussed above, it would be interesting to apply the same NMR techniques to explore the metabolomics of different Wolbachia strain/host pairings, such as facultative Wolbachia strains that infect filarial nematodes, wMel that have been established in novel insect hosts, or Wolbachia strains (e.g., wAu) that impose no obvious effect on host reproduction (Hoffmann et al, 1996;Cao et al, 2019). Moreover, extending such investigations to pairings of Wolbachia and Aedes aegypti would be interesting, given the potential of the former in limiting the spread of tropical diseases carried by the latter (McGraw and O'Neill, 2013;O'Neill et al, 2018;Ryan et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…Apart from their direct manipulation as suggested above, the involvement of both the IIS and hypoxia signaling pathways as a consequence of Wolbachia infection opens up several exciting avenues for further discovery. Given the strain-host specificity discussed above, it would be interesting to apply the same NMR techniques to explore the metabolomics of different Wolbachia strain/host pairings, such as facultative Wolbachia strains that infect filarial nematodes, wMel that have been established in novel insect hosts, or Wolbachia strains (e.g., wAu) that impose no obvious effect on host reproduction (Hoffmann et al, 1996;Cao et al, 2019). Moreover, extending such investigations to pairings of Wolbachia and Aedes aegypti would be interesting, given the potential of the former in limiting the spread of tropical diseases carried by the latter (McGraw and O'Neill, 2013;O'Neill et al, 2018;Ryan et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…Cytoplasmic incompatibility results in fewer viable offspring in crosses between Wolbachia-infected males and uninfected females. Wolbachia may also provide fitness advantages through the protection of hosts against viruses (Teixeira et al, 2008, Hedges et al, 2008, nutritional provisioning (Brownlie et al, 2009), increased fertility (Dobson et al, 2002) or changes in life history (Cao et al, 2019).…”
mentioning
confidence: 99%
“…To complement the view of Wolbachia fitness effects on its host, future experiments should be conducted under more demanding conditions, e.g., food limitation, high competition, and enemy presence (Brownlie et al, 2009;Gavotte et al, 2010;Vorburger and Gouskov, 2011), and on earlier developmental stages (Da et al, 2016). For example, Cao et al (2019) found that Wolbachia provides fitness advantages to its Drosophila simulans host only when breeding on fungi-infected fruits. In another example, Brownlie et al (2009) showed that Wolbachia infection confers a positive fecundity benefit for D. melanogaster only when they were reared on iron-restricted or overloaded diets.…”
Section: Hypothesis 1 Is Not Supported: the Interaction With The Endomentioning
confidence: 99%
“…One possible explanation is related to the tendency of the endosymbiont-host relationships to evolve into a full dependence of the host on the endosymbiont for its survival and reproduction in the form of obligatory relationships (Moran et al, 2008;Ferrari and Vavre, 2011). However, endosymbionts may promote persistence even when the host is not fully dependent on them, for example, by providing fitness advantages to the host, e.g., nutrient supplementation or protection from enemies (Feldhaar, 2011;Su et al, 2013;Cao et al, 2019). A third possible group of mechanisms is related to reproductive manipulations imposed by the endosymbiont on the host's reproduction to enhance its own transmission (Werren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%